2007
DOI: 10.1002/hec.1310
|View full text |Cite
|
Sign up to set email alerts
|

Publicly funded medical savings accounts: expenditure and distributional impacts in Ontario, Canada

Abstract: This paper presents the findings from simulations of the introduction of publicly funded medical savings accounts (MSAs) in the province of Ontario, Canada. The analysis exploits a unique data set linking population-based health survey information with individual-level information on all physician services and hospital services utilization over a four-year period. The analysis provides greater detail along three dimensions than have previous analyses: (1) the distributional impacts of publicly funded MSAs acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Most of the literature on the burden and complexity of comorbidity in the context of an index condition is published in specialty-specific journals that are typically not easily synthesized across specialties. Drawing general inferences from multimorbidity literature is further complicated by the use of different study designs, multimoribidty definitions, and data sources [18]. In this paper we draw general insights about multimorbidity by observing patterns of comorbidity and associated health care utilization and costs from three community-based cohorts with three distinct index conditions [1517].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the literature on the burden and complexity of comorbidity in the context of an index condition is published in specialty-specific journals that are typically not easily synthesized across specialties. Drawing general inferences from multimorbidity literature is further complicated by the use of different study designs, multimoribidty definitions, and data sources [18]. In this paper we draw general insights about multimorbidity by observing patterns of comorbidity and associated health care utilization and costs from three community-based cohorts with three distinct index conditions [1517].…”
Section: Discussionmentioning
confidence: 99%
“…The original studies were conducted on populations residing in Ontario, Canada’s most populous province with approximately 13 million residents. The provincial government is the sole insurer for medically necessary physician and hospital services through the provincial health insurance plan (OHIP), with over 98% of all physician expenditures and over 93% of all hospital expenditures being publicly financed [18]. As such the majority of health services used by Ontarians are captured in administrative data holdings.…”
Section: Methodsmentioning
confidence: 99%
“…The empirical literature has shown that a range of factors influences health care spending (Di Matteo & Di Matteo, 1998;Ellis et al, 2013;Hurley et al, 2008;Shang & Goldman, 2008). Age and gender are the most commonly used characteristics in payment models.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Existing empirical literature has shown that a range of factors influence health care spending (Di Matteo & Di Matteo, 1998;Ellis, Fiebig, Johar, Jones, & Savage, 2013;Hurley, Guindon, Rynard, & Morgan, 2008;Shang & Goldman, 2008). As our model would be applied to risk-adjusted capitation design, we follow the risk adjustment literature to use age, gender, and diagnostic information as main predicting factors.…”
mentioning
confidence: 99%
“…In Europe the MSA concept has also been considered from a scientific approach (Henke and Borchardt, 2003), as well as from a practical perspective (Dixon, 2002;Johannssen, 2003;Kiszka and Sowada, 2007). Consequently, there are positive and negative findings about possible effects of implementing this form of financing into the contemporary health care systems (Saltman, 1998;Hurley at al., 2008;Kiszka and Sowada, 2007;Borda, 2009). The purpose of the paper is to present the idea of Medical Savings Accounts and to examine the possibilities of MSAs incorporation into health care systems in European countries.…”
Section: Introductionmentioning
confidence: 99%